1992
DOI: 10.1104/pp.99.3.895
|View full text |Cite
|
Sign up to set email alerts
|

Repression of the Plastidic Isoenzymes of Aldolase, 3-Phosphoglycerate Kinase, and Triosephosphate Isomerase in the Barley Mutant “albostrians”

Abstract: White leaves of the mutant line albostrians and green leaves of the wild-type cultivar Salome of barley (Hordeum vulgare L.) were screened for the presence of plastidic and cytosolic isoenzymes of sugar-phosphate metabolism. lsoenzyme separation was achieved by anion-exchange chromatography on Fractogel TSK DEAE-650(S). The mutant tissue had a markedly reduced level of plastidic 3-phosphoglycerate kinase, triosephosphate isomerase, and aldolase activity. In contrast, the activity of plastidic glucosephosphate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…On greening of etiolated barley leaves the rise of PGK was almost entirely the result of an increase in the chloroplastic isoenzyme. In contrast, in the pigmentless leaf sectors of the mutant the chloroplastic PGK content was only 10% of that in green leaves, thus confirming a recent report by Boldt et al (1992), while the cytosolic isoenzyme of the mutant was more than double that of green leaves. Table 2 shows a substantial presence of plastid PGK isoenzymes in roots of barley, equivalent to 1.1 units 9 (g FW) 1, though most of the PGK activity belonged to the cytosolic isoenzyme.…”
Section: Resultssupporting
confidence: 73%
“…On greening of etiolated barley leaves the rise of PGK was almost entirely the result of an increase in the chloroplastic isoenzyme. In contrast, in the pigmentless leaf sectors of the mutant the chloroplastic PGK content was only 10% of that in green leaves, thus confirming a recent report by Boldt et al (1992), while the cytosolic isoenzyme of the mutant was more than double that of green leaves. Table 2 shows a substantial presence of plastid PGK isoenzymes in roots of barley, equivalent to 1.1 units 9 (g FW) 1, though most of the PGK activity belonged to the cytosolic isoenzyme.…”
Section: Resultssupporting
confidence: 73%
“…2D). The phenotypes that we observed in these two cases are in close agreement with previous reports on the effects of reduction of the levels of these gene products (Boldt et al, 1992;Tanaka et al, 1999).…”
Section: Developmental Phenotypes Revealed By Silencing 400 Tomato Estssupporting
confidence: 82%
“…In pigment-deficient leaves of the chloroplast-ribosomedeficient barley mutant albostrians, only significantly reduced concentrations were measured for several nuclear encoded proteins which are targeted to plastids (Calvin cycle enzymes; Bradbeer et al 1979), functionally associated to the plastid (nitrate reductase; Bo¨rner et al 1986), or to the peroxisome (glycolate oxidase, catalase, hydroxy pyruvate reductase; Boldt et al 1992;Boldt et al 1997). Using nuclear run-on transcription assays and Northern blot hybridization it was eventually shown that the downregulation occurred at the level of transcription (Hess et al 1991(Hess et al , 1994.…”
Section: Plastid Protein Synthesis Is Required For the Expression Of mentioning
confidence: 99%